Lemma 56.13.3. Let $F$ and $F'$ be siblings as in Definition 56.13.1. Then

if $F$ is essentially surjective, then $F'$ is essentially surjective,

if $F$ is fully faithful, then $F'$ is fully faithful.

Lemma 56.13.3. Let $F$ and $F'$ be siblings as in Definition 56.13.1. Then

if $F$ is essentially surjective, then $F'$ is essentially surjective,

if $F$ is fully faithful, then $F'$ is fully faithful.

**Proof.**
Part (1) is immediate from property (2) for siblings.

Assume $F$ is fully faithful. Denote $\mathcal{D}' \subset \mathcal{D}$ the essential image of $F$ so that $F : D^ b(\mathcal{A}) \to \mathcal{D}'$ is an equivalence. Since the functor $F'$ factors through $\mathcal{D}'$ by property (2) for siblings, we can consider the functor $H = F^{-1} \circ F' : D^ b(\mathcal{A}) \to D^ b(\mathcal{A})$. Observe that $H$ is a sibling of the identity functor. Since it suffices to prove that $H$ is fully faithful, we reduce to the problem discussed in the next paragraph.

Set $\mathcal{D} = D^ b(\mathcal{A})$. We have to show a sibling $F : \mathcal{D} \to \mathcal{D}$ of the identity functor is fully faithful. Denote $a_ X : X \to F(X)$ the functorial isomorphism for $X \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A})$ given to us by Definition 56.13.1. For any $K$ in $\mathcal{D}$ and distinguished triangle $K_1 \to K_2 \to K_3$ of $\mathcal{D}$ if the maps

\[ F : \mathop{\mathrm{Hom}}\nolimits (K, K_ i[n]) \to \mathop{\mathrm{Hom}}\nolimits (F(K), F(K_ i[n])) \]

are isomorphisms for all $n \in \mathbf{Z}$ and $i = 1, 3$, then the same is true for $i = 2$ and all $n \in \mathbf{Z}$. This uses the $5$-lemma Homology, Lemma 12.5.20 and Derived Categories, Lemma 13.4.2; details omitted. Similarly, if the maps

\[ F : \mathop{\mathrm{Hom}}\nolimits (K_ i[n], K) \to \mathop{\mathrm{Hom}}\nolimits (F(K_ i[n]), F(K)) \]

are isomorphisms for all $n \in \mathbf{Z}$ and $i = 1, 3$, then the same is true for $i = 2$ and all $n \in \mathbf{Z}$. Using the canonical truncations and induction on the number of nonzero cohomology objects, we see that it is enough to show

\[ F : \mathop{\mathrm{Ext}}\nolimits ^ q(X, Y) \to \mathop{\mathrm{Ext}}\nolimits ^ q(F(X), F(Y)) \]

is bijective for all $X, Y \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A})$ and all $q \in \mathbf{Z}$. Since $F$ is a sibling of $\text{id}$ we have $F(X) \cong X$ and $F(Y) \cong Y$ hence the right hand side is zero for $q < 0$. The case $q = 0$ is OK by our assumption that $F$ is a sibling of the identity functor. It remains to prove the cases $q > 0$.

The case $q = 1$: Injectivity. An element $\xi $ of $\mathop{\mathrm{Ext}}\nolimits ^1(X, Y)$ gives rise to a distinguished triangle

\[ Y \to E \to X \xrightarrow {\xi } Y[1] \]

Observe that $E \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A})$. Since $F$ is a sibling of the identity functor we obtain a commutative diagram

\[ \xymatrix{ E \ar[d] \ar[r] & X \ar[d] \\ F(E) \ar[r] & F(X) } \]

whose vertical arrows are the isomorphisms $a_ E$ and $a_ X$. By TR3 the distinguished triangle associated to $\xi $ we started with is isomorphic to the distinguished triangle

\[ F(Y) \to F(E) \to F(X) \xrightarrow {F(\xi )} F(Y[1]) = F(Y)[1] \]

Thus $\xi = 0$ if and only if $F(\xi )$ is zero, i.e., we see that $F : \mathop{\mathrm{Ext}}\nolimits ^1(X, Y) \to \mathop{\mathrm{Ext}}\nolimits ^1(F(X), F(Y))$ is injective.

The case $q = 1$: Surjectivity. Let $\theta $ be an element of $\mathop{\mathrm{Ext}}\nolimits ^1(F(X), F(Y))$. This defines an extension of $F(X)$ by $F(Y)$ in $\mathcal{A}$ which we may write as $F(E)$ as $F$ is a sibling of the identity functor. We thus get a distinguished triangle

\[ F(Y) \xrightarrow {F(\alpha )} F(E) \xrightarrow {F(\beta )} F(X) \xrightarrow {\theta } F(Y[1]) = F(Y)[1] \]

for some morphisms $\alpha : Y \to E$ and $\beta : E \to X$. Since $F$ is a sibling of the identity functor, the sequence $0 \to Y \to E \to X \to 0$ is a short exact sequence in $\mathcal{A}$! Hence we obtain a distinguished triangle

\[ Y \xrightarrow {\alpha } E \xrightarrow {\beta } X \xrightarrow {\delta } Y[1] \]

for some morphism $\delta : X \to Y[1]$. Applying the exact functor $F$ we obtain the distinguished triangle

\[ F(Y) \xrightarrow {F(\alpha )} F(E) \xrightarrow {F(\beta )} F(X) \xrightarrow {F(\delta )} F(Y)[1] \]

Arguing as above, we see that these triangles are isomorphic. Hence there exists a commutative diagram

\[ \xymatrix{ F(X) \ar[d]^\gamma \ar[r]_{F(\delta )} & F(Y[1]) \ar[d]_\epsilon \\ F(X) \ar[r]^\theta & F(Y[1]) } \]

for some isomorphisms $\gamma $, $\epsilon $ (we can say more but we won't need more information). We may write $\gamma = F(\gamma ')$ and $\epsilon = F(\epsilon ')$. Then we have $\theta = F(\epsilon ' \circ \delta \circ (\gamma ')^{-1})$ and we see the surjectivity holds.

The case $q > 1$: surjectivity. Using Yoneda extensions, see Derived Categories, Section 13.27, we find that for any element $\xi $ in $\mathop{\mathrm{Ext}}\nolimits ^ q(F(X), F(Y))$ we can find $F(X) = B_0, B_1, \ldots , B_{q - 1}, B_ q = F(Y) \in \mathop{\mathrm{Ob}}\nolimits (\mathcal{A})$ and elements

\[ \xi _ i \in \mathop{\mathrm{Ext}}\nolimits ^1(B_{i - 1}, B_ i) \]

such that $\xi $ is the composition $\xi _ q \circ \ldots \circ \xi _1$. Write $B_ i = F(A_ i)$ (of course we have $A_ i = B_ i$ but we don't need to use this) so that

\[ \xi _ i = F(\eta _ i) \in \mathop{\mathrm{Ext}}\nolimits ^1(F(A_{i - 1}), F(A_ i)) \quad \text{with}\quad \eta _ i \in \mathop{\mathrm{Ext}}\nolimits ^1(A_{i - 1}, A_ i) \]

by surjectivity for $q = 1$. Then $\eta = \eta _ q \circ \ldots \circ \eta _1$ is an element of $\mathop{\mathrm{Ext}}\nolimits ^ q(X, Y)$ with $F(\eta ) = \xi $.

The case $q > 1$: injectivity. An element $\xi $ of $\mathop{\mathrm{Ext}}\nolimits ^ q(X, Y)$ gives rise to a distinguished triangle

\[ Y[q - 1] \to E \to X \xrightarrow {\xi } Y[q] \]

Applying $F$ we obtain a distinguished triangle

\[ F(Y)[q - 1] \to F(E) \to F(X) \xrightarrow {F(\xi )} F(Y)[q] \]

If $F(\xi ) = 0$, then $F(E) \cong F(Y)[q - 1] \oplus F(X)$ in $\mathcal{D}$, see Derived Categories, Lemma 13.4.11. Since $F$ is a sibling of the identity functor we have $E \cong F(E)$ and hence

\[ E \cong F(E) \cong F(Y)[q - 1] \oplus F(X) \cong Y[q - 1] \oplus X \]

In other words, $E$ is isomorphic to the direct sum of its cohomology objects. This implies that the initial distinguished triangle is split, i.e., $\xi = 0$. $\square$

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)